Indocyanine green‐fluorescent imaging for a detection of accessory pancreatic duct in pancreas‐preserving duodenectomy. Issue 2 (11th September 2022) - Ito, Ryota; Mise, Yoshihiro; Tanaka, Haruka; Miyashita, Mamiko; Saiura, Akio
Abstract: Pancreas‐preserving duodenectomy is indicated for select patients with a duodenal tumor in the second portion. In this procedure, identification and closure of the accessory pancreatic duct is important to prevent postoperative pancreatic fistula. A 63‐y‐old man was diagnosed with duodenal mucosal carcinoma in the second portion, with invasion of the major ampullary. We performed pancreas‐preserving duodenectomy. Intraoperatively, indocyanine green‐fluorescent imaging identified the accessory pancreatic duct clearly and it was successfully closed. Postoperative pancreatic fistula did not occur. Indocyanine green‐fluorescent imaging is effective in identifying the accessory pancreatic duct in pancreas‐preserving duodenectomy. Abstract : In pancreas‐preserving duodenectomy, identification and closure of the accessory pancreatic duct is important to prevent postoperative pancreatic fistula. Here, we describe a new method for identifying the accessory pancreatic duct. The injection of ICG into the main pancreatic duct clearly detected the accessory pancreatic duct.